Ups and downs - Buenaventura, Patricia Gabrielle S. (College of Arts and Letters, University of the Philippines Diliman, 2018)
Children's fiction is a tool to expose children to new experiences while teaching valuable life lessons. Recently, children's fiction began opened itself up to being more than just a tool for education but also for breaking down barriers and changing perceptions. In particular, children's fiction has become a medium where PWDs can promote awareness about their experiences as well as influence them to have a positive way of looking at PWDs. This paper attempts to present the current perceptions of Filipinos towards PWDs, explain how children's fiction can be used as a tool for awareness and influence, stress the importance of crafting characters with disabilities positively and realistically, as well as provide ways to craft these characters as such.